The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/medicina59030453
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Iron-Chelating Therapy in Improving Neurological Outcome in Patients with Intracerebral Hemorrhage: Evidence-Based Case Report

Abstract: Current primary intracerebral hemorrhage (ICH) treatments focus on limiting hematoma volume by lowering blood pressure, reversing anticoagulation, or hematoma evacuation. Nevertheless, there is no effective strategy to protect the brain from secondary injury due to ICH. Excess heme and iron as by-products of lysing clots in ICH might contribute to this secondary injury by triggering perihematomal edema. We present a clinical situation of an ICH case where iron-chelating therapy might be beneficial, as supporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Given the nephrotoxicity and cardiotoxicity associated with iron chelators, their usage is currently limited to experimental settings [ 179 ]. Furthermore, there is a need for additional research to explore the clinical applicability and long-term outcomes of iron chelation therapy in TBI patients [ 180 ].…”
Section: Reviewmentioning
confidence: 99%
“…Given the nephrotoxicity and cardiotoxicity associated with iron chelators, their usage is currently limited to experimental settings [ 179 ]. Furthermore, there is a need for additional research to explore the clinical applicability and long-term outcomes of iron chelation therapy in TBI patients [ 180 ].…”
Section: Reviewmentioning
confidence: 99%
“…The "mass effect," inflammatory responses, and iron-induced secondary damage (Jiang et al, 2020) necessitate medical interventions targeting secondary injury. These include anti-inflammatory agents (Ironside et al, 2021) and iron chelating agents (Ramadhan et al, 2023). Surgical evacuation of the hematoma represents a therapeutic approach for cerebral hemorrhage.…”
Section: Introductionmentioning
confidence: 99%
“…This trial suggested safety and hinted at therapeutic efficacy in humans, which is promising for the diffusion of this potential therapy from "bench to bedside." (16,19,20).…”
mentioning
confidence: 99%